Visualization of Mapbox Vector Tiles in a CesiumJS Virtual Globe Environment - Kang Kuk (Research Advances in Environment, Geography and Earth Science Vol. 5, 2024)
This study presents a technique for visualizing Map-box vector tiles in a 3D virtual environment. The hosting of vector tiles on CartoDB/Bigquery and the process for producing them are detailed. Vector data is used extensively in geographic information systems (GIS) to analyse and administrate virtual landscapes. Essentially, CesiumJS—which can be accessed through the link, http://cesiumjs.org, is an open-source JavaScript library for creating a virtual globe environment in performance-effective, high-quality rendering, precision, and user-friendly. It is a wonderful tool for 3D-themed visualizations of the earth. CesiumJS has a number of data sources, but none of them supports vector tile format. CartoDB/BigQuery hosts vector tiles and a process for producing vector tiles from massive vector data using the BigQuery tiler of CartoDB has been provided. The findings imply that the suggested CartoDB vector tiler, as opposed to the conventional vector database method, can assist us in more effectively visualizing vector tiles on CesiumJS Web Globe.